Enquête sur les jardins et savoirs jardiniers de La Réunion : premiers résultats d’une recherche sur la biodiversité « cultivée » - Sébastien Clément (Développement Durable et Territoires)
This article, resulting from doctoral research, proposes to bring landmarks on the dynamics of biodiversity in the private gardens of Reunion Island. The aim is to examine the conditions for the production of a "cultivated" biodiversity, which is inseparable from the local way of life, from the knowledge and know-how inscribed in cultural heritages, and from the social relations woven around the gardens. The approach proposes the study of a measurement of the level of biodiversity through a precise scientific protocol combined with the analysis of practices and knowledge invested in the creation and maintenance of gardens. This approach makes it possible to evaluate the impact of the transmission of gardeners' knowledge and their interactions with living species. It is based on interviews with gardeners and on an experiment consisting of the collective creation of a garden on an uncultivated plot in the west of the island at an altitude of 350 meters, and a quantitative survey of changes in the species of flora and fauna. The initial results of this research reveal an increase in the number of species and the genesis of a "cultivated" biodiversity.